A Defined Antigen Skin Test for Diagnosis of Bovine Tuberculosis in Domestic Water Buffaloes (Bubalus bubalis) - Kumar, Tarun; Singh, Mahavir; Jangir, Babu Lal; Arora, Devan; Srinivasan, Sreenidhi; Bidhan, Devender; Yadav, Dipin Chander; Veerasami, Maroudam; Bakker, Douwe; Kapur, Vivek; Jindal, Naresh (Frontiers in Veterinary Science, 2021)
Bovine tuberculosis (bTB) remains endemic in domestic water buffaloes (Bubalus bubalis) in India and elsewhere, with limited options for control other than testing and slaughter. The prescribed tuberculin skin tests with purified protein derivative (PPD) for diagnosis of bTB preclude the use of Bacille Calmette-Guérin (BCG)-based vaccination because of the antigenic cross-reactivity of vaccine strains with Mycobacterium bovis and related pathogenic members of the M. tuberculosis complex (MTBC). For the diagnosis of bTB in water buffaloes, we here assessed a recently described defined-antigen skin test (DST) that comprises overlapping peptides representing the ESAT-6, CFP-10 and Rv3615c antigens, present in disease-causing members of the MTBC but missing in BCG strains. The performance characteristics of three doses (5 μg, 10 μg or 20 μg / peptide) of the DST were assessed in natural tuberculin skin test reactor (n = 11) and non-reactor (n = 35) water buffaloes at a university dairy farm in Hisar, India, and results were compared with the single intradermal skin test (SIT). The results showed a dose-dependent response of DST in natural reactor water buffalo, although the SIT induced a significantly greater (P <0.001) skin test response than the highest dose of DST used. However, using a cut-off of 2 mm or greater, the 5 μg, 10 μg and 20 μg DST cocktail correctly classified eight, 10 and all 11 of the SIT-positive reactors, respectively, suggesting that the 20 μg DST cocktail has a diagnostic sensitivity (Se) of 1.0 (95% CI: 0.72 – 1.0) identical to that of the SIT. Importantly, none of the tested DST doses induced any measurable skin induration responses in the 35 SIT-negative animals, suggesting a specificity point estimate of 1.0 (95% CI:0.9 - 1.0), also identical to that of the SIT and compares favorably with that of the comparative cervical test (Se = 0.85; 95% CI:0.55 – 0.98). Overall, the results suggest that the DST enables sensitive and specific diagnosis of bTB in water buffaloes. Future field trials to explore the utility of DST as a replacement for tuberculin in routine surveillance programs and to enable BCG vaccination of water buffalo are warranted.